2021
DOI: 10.1167/iovs.62.9.21
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt Signaling Drives Myopia Development and Can Be Pharmacologically Modulated

Abstract: The purpose of this study was to evaluate the role of the canonical Wnt signaling in the development of the myopia. METHODS.Plasma from adult patients with myopia, myopic animal models including the adenomatous polyposis coli (APC) gene mutation mouse model, and the form deprivation (FD) induced mouse model of myopia were used. Niclosamide, a canonical Wnt pathway inhibitor, was orally administrated in animal models. Plasma levels of DKK-1 were determined by using enzyme-linked immunosorbent assay. Refraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In addition, an animal study by a Liu et al . found that niclosamide could effectively inhibit the progression of myopia [ 5 ]. Patients consume 2 g for up to 7 days for the treatment of intestinal parasites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an animal study by a Liu et al . found that niclosamide could effectively inhibit the progression of myopia [ 5 ]. Patients consume 2 g for up to 7 days for the treatment of intestinal parasites.…”
Section: Discussionmentioning
confidence: 99%
“…This drug kills tapeworms by inhibiting oxidative phosphorylation in the mitochondria and anaerobic adenosine triphosphate (ATP) production [ 1 ]. Recent studies have shown its potential in treating many other diseases including Parkinson’s disease, diabetes, viral and microbial infections, and inhibition of myopia progression [ 2 5 ]. In addition, other studies have demonstrated the efficacy of niclosamide in the treatment of various cancers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When abnormalities in reactive oxygen species generation result in an imbalance in redox reactions in the body, vitamin E may modulate the relevant signaling pathways (24)(25)(26). The extracellular regulated protein kinase (ERK)1/2-matrix metalloproteinase (MMP)-2, Wnt, and Akt pathways are involved in the regulation of myopia (27)(28)(29). The Wnt pathway is continuously activated in myopia in mice, causing a decrease in the expression of the Wnt inhibitor DKK-1 (27).…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular regulated protein kinase (ERK)1/2-matrix metalloproteinase (MMP)-2, Wnt, and Akt pathways are involved in the regulation of myopia (27)(28)(29). The Wnt pathway is continuously activated in myopia in mice, causing a decrease in the expression of the Wnt inhibitor DKK-1 (27). Inhibition of the Wnt pathway after niclosamide treatment eventually leads to a decrease in myopia development, a regulatory function not found with α-tocopherol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this, we concluded that the regulation of dopaminergic genes reflected a mechanism in which vmat2 upregulation compensates functional deficits of dopaminergic synapses utilizing D2-receptor family genes. Experimental evidence and genome-wide association studies imply the canonical Wnt signaling pathway in eye development and eye disorders such as myopia (Cheng et al, 2013;Liu et al, 2021). A potential correlation between Cx35.1 and the canonical Wnt-signaling pathway affecting eye-development was testable based on a previous RNA-seq expression analysis showing expression of wingless-type MMTV integration site family and frizzled class receptor genes in 6dpf TL larvae (GEO database entry GSE181853) (Supplementary Table S4).…”
Section: Gjd2b/cx351 Regulates Wnt and Dopamine Receptor Gene Expressionmentioning
confidence: 99%